Serving the right menu of R&D policy instruments to firms: An analysis of policy mix sequencing - Helena Lenihahn; Kevin Mulligan; Mauricio Perez-Alaniz; Christian Rammer (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
The R&D policy instrument mix concept has become increasingly important for understanding how public R&D support drives firm-level R&D. To-date, empirical studies have conceptualised the instrument mix as a static unit, whereby firms receive multiple policy instruments at one point in time. However, firms can also receive multiple instruments in a sequence, over time. While sequencing is well rehearsed heoretically, this remains a major gap in the empirical literature. Our study evaluates, for the first time, how R&D policy instrument mix sequencing impacts firm-level R&D. We construct a unique dataset, containing almost 25,000 firm-year observations over a 17-year period for Ireland. Our analysis focuses on R&D grants, R&D tax credits, and publicly-supported academic-industry collaborations, and develops two novel approaches to measure R&D policy instrument mix sequencing. Our results suggest that R&D policy instrument mix sequencing is highly effective at driving firm-level R&D, but that some sequences are more effective than others. These findings highlight opportunities to realise superior policy outcomes through targeted sequencing.
Keywords: O25; O30; D04; O38; D22; O31; 330; Policy mix; Policy instrument mix sequencing; Public R&D support; R&D grant; R&D tax credit; Academic-industry collaboration